Stress system changes associated with marijuana dependence may increase craving for alcohol and cocaine - Fox, Helen C. (2012)
OBJECTIVE: To date, little research exists defining bio-behavioral adaptations associated with both marijuana abuse and risk of craving and relapse to other drugs of abuse during early abstinence. METHOD: Fifty-nine treatment-seeking individuals dependent on alcohol and cocaine were recruited. Thirty of these individuals were also marijuana (MJ) dependent; 29 were not. Twenty-six socially drinking healthy controls were also recruited. All participants were exposed to three 5-min guided imagery conditions (stress, alcohol/cocaine cue and relaxing), presented randomly, one per day across three consecutive days. Measures of craving, anxiety, heart rate, blood pressure, plasma adrenocorticotrophic hormone and cortisol were collected at baseline and subsequent recovery time points. RESULTS: The MJ-dependent group showed increased basal anxiety ratings and cardiovascular output alongside enhanced alcohol craving and cocaine craving, and dampened cardiovascular response to stress and cue. They also demonstrated elevated cue-induced anxiety and stress-induced cortisol and adrenocorticotrophic hormone levels, which were not observed in the non-MJ-dependent group or controls. Cue-related alcohol craving and anxiety were both predictive of a shorter number of days to marijuana relapse following discharge from inpatient treatment. CONCLUSIONS: Findings provide some support for drug cross-sensitization in terms of motivational processes associated with stress-related and cue-related craving and relapse.